Biodegradable electrospun PLLA fibers containing the mosquito-repellent DEET. (April 2019) - Bonadies, Irene; Longo, Alessandra; Androsch, René; Jehnichen, Dieter; Göbel, Michael; Di Lorenzo, Maria Laura
Graphical abstract: Highlights: This is the first literature example of electrospun PLLA fibers containing DEET. The biodegradable fibers are defect-free with uniform diameter of 1 µm. It is possible to incorporate more than 50 wt% of DEET into electrospun PLLA. Evaporation of DEET is delayed in the electrospun PLLA fibers. PLLA/DEET fibers can be used as tools for fighting mosquito-caused diseases. Abstract: The manuscript details the first literature example of fibers of poly(l -lactic acid) (PLLA) containing a mosquito repellent agent, N, N -diethyl-3-methylbenzamide (DEET). The fibers were prepared by electrospinning, are defect-free and have uniform diameter of the order of magnitude of 1 µm. Thermogravimetry and infrared spectroscopy showed that it is possible to incorporate more than 50 wt% of DEET, which is then slowly released to the environment. As such, the fibers can function as a drug delivery device. Further structural analyses disclosed that PLLA in DEET-containing fibers is semicrystalline, and contains α-crystals formed during electrospinning. Thermal, morphological and structural characterization revealed that the PLLA/DEET electrospun fibers have potential as novel material for controlled release of DEET, which, coupled with the ease of fabrication, detailed here, can provide innovative tools for fighting mosquito-caused diseases.